The Influence of peer pressure and parent-child communication on the initiation of teenage sexual activity among secondary school students in Benue State (2009)
This is a correlation research to find out the effects of peer pressure and parent-child communication on teenage sexual initiation among in-school adolescents in Benue State. Stratified random sampling was used to select 151 males and 166 females, totalling 317 adolescents from secondary schools in Benue state. A self-administered questionnaire tagged Teenage Sexual Activity Initiation Scale (TSAI) was used to collect data from the study sample. The scale had a reliability coefficient of 0.62. The mean age of the students was 16 years. The findings showed that there were positive significant relationships between peer pressure and initiation of sexual activity. The study has implication for family life education. Programmes should be planned to delay early initiation of sexual activity. Abstinence education should be encouraged in the schools.